Shifting Frontiers across Cinema and Literature : Nathalie Léger’s Suite for Barbara Loden - Karácsonyi, Judit (AMERICANA E-journal of American Studies in Hungary, 2024)
Reflections on the relationship between film and literature seem to focus on film adaptations, while the transformation of a film into a novel remains a less known practice. In my paper, I propose to address some of the questions raised by Nathalie Léger’s contemporary literary novelisation, Suite for Barbara Loden. While examining how this type of adaptation establishes an intermedial dialogue between cinema and literature, I intend to explore how the operation of modulation allows the filmic narrative to become more than a simple “mould for the novelistic hypotext”, to become the pre/text for the literature it inspires and within which the film “takes form and finds its reflection”.